A Comprehensive Study on Identification of Human Age Face Features - Rajamanickam, Leelavathi; Parthasarathy, Rajamohan; Sulaiman, Nor Anis Asma Binti (International Journal of Psychosocial Rehabilitation, 2020)
Research on age estimation draws more attention, face recognition is challenging and interesting. Facial images provide a lot of information such as age gender etc., Appearances of facial images are different from person to person, eyes are used for extracting gender and facial expression. Age estimation methods are tested on predefined or existing facial image. Age estimation is divided into two categories; classification based and regression based. Applying of the existing methods on facial images the results differ to equipment used such as phone, camera, laptop and the quality of the camera used to capture the facial image. Facial age feature helps in finding the missing persons. Human age estimation also helps in employments to find the person’s age for retirement. This paper gives the identification of human age estimation through facial features.